Chemical compositions of Commiphora opobalsamum stem bark to alleviate liver complications in streptozotocin-induced diabetes in rats: Role of oxidative stress and DNA damage. (14th October 2022) - Farid, Mai M.; Aboul Naser, Asmaa F.; Salem, Maha M.; Ahmed, Yomna R.; Emam, Mahmoud; Hamed, Manal A.
Abstract: Context: Hyperglycaemia plays an important role in the development of non-alcoholic fatty liver disease, which is a common complication in diabetics. Objective: The present study aimed to investigate the chemical composition and the efficacy of Commiphora opobalsamum stem bark butanol fraction in ameliorating liver injury associated with diabetes induced by streptozotocin (STZ) in rats. Materials and methods: The butanol fraction was applied to high-performance liquid chromatography-mass spectrometry (HPLC/MS n ) to identify the most bioactive metabolites. Diabetes was induced by a single intraperitoneal injection of STZ (60 mg/kg body weight), while treatment with the plant extract was performed (100 mg/kg body weight) for three weeks after diabetic induction for one month. Results: Thirty eight metabolites were tentatively identified from the butanol fraction of C. opobalsamum stem bark. Insulin, glutathione, superoxide dismutase, and high density lipoprotein levels in diabetic rats were significantly low ( p <  0.05), while glucose, α-amylase, malondialdehyde, aspartate and alanine aminotransferases, cholesterol, triglycerides, low density lipoprotein, tumour necrosis factor-α, interleukin-6, and DNA fragmentation levels were significantly high. Treatment with the plant extract showed improvements in the seleced parameters by variable degrees. Conclusion: The plant extract is considered as a promising natural therapeutic agent against liver injury, hyperglycemia, oxidative stress, inflammation, hyperlipidaemia, and DNA damage. Graphical Abstract: UF0001